2009
DOI: 10.1080/00365520802116422
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variance in childhood coeliac disease and the HLA-DQ/DR dose effect

Abstract: No correlation was found between disease severity and a double HLA-DQ2 gene dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
3
20
1
3
Order By: Relevance
“…As expected the HLA-DQ2 homozygous status, or anyway associated with a b2 chain double dose (DQ2,B1*02/*02), leads to the highest risk to develop CD which in our study was 1:7 vs. 1:47 in DQ2 heterozygous subjects. These data are concordant with what is affirmed by many authors (3,12,(19)(20)(21), while Megiorni et al (10) found the highest risk value for DQ2 and DQ8 positive subjects. In our experience these individuals are comprised in an intermediate risk category (1:41).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As expected the HLA-DQ2 homozygous status, or anyway associated with a b2 chain double dose (DQ2,B1*02/*02), leads to the highest risk to develop CD which in our study was 1:7 vs. 1:47 in DQ2 heterozygous subjects. These data are concordant with what is affirmed by many authors (3,12,(19)(20)(21), while Megiorni et al (10) found the highest risk value for DQ2 and DQ8 positive subjects. In our experience these individuals are comprised in an intermediate risk category (1:41).…”
Section: Discussionsupporting
confidence: 82%
“…We showed how the presence of DQB1*02 allele (b2 chain) in DQ8 positive individuals increases the risk of developing CD twofold (from 1:85 to 1:43). DQB1*02 heterozygous subjects (b2, B1*02/X) are comprised in a low risk category (1:75), together with subjects DQ8 positive when DQB1*02 and DQB1*0302 negative (1:85), in line with what was observed by other authors (3,19) and in contrast with Megiorni et al (10) who found a risk lower for b2 heterozygous subjects than in the general population. Values lower than the disease prevalence in the general population were demonstrated for a5 subjects (1: 1818) or DQ2, DQ8, b2, a5 negative subjects (1:3580).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…As expected, and according to other authors (15,25,(30)(31)(32)(33)(34), the DQ2 homozygous status (category XIV) had the highest risk for CD (1:10 in children and adults patients); next in risk level were the DQ2 heterozygous categories with no DQ8 (XI, XII and V); categories with DQ8 in homozygosis or heterozygosis with DQB01*02 (VII, X and VIII) had a lower risk. When we analyzed celiac children and adults separately, the risk was different.…”
Section: Discussionsupporting
confidence: 57%
“…There are several studies that demonstrate that isolated DQB1*02 would confer a predisposition towards triggering CD (15,25,26,30,31,(36)(37)(38)(39), and the presence of isolated DQA1*05 would not (15,22,25). In our study, 1 % of celiac children and 1.4 % of adults presented isolated DQB1*02 compared to healthy controls (11.1 % of cases).…”
Section: Discussionmentioning
confidence: 67%